Larry ups the ante. (Economist, 2004)
The author explains why Larry Ellison, founder and head of software giant Oracle, is determined to acquire rival firm PeopleSoft. Despite the millions of dollars that Larry Ellison, the boss of Oracle, has spent pursuing PeopleSoft, a rival business-software firm, doubts about the sincerity of his hostile bid have lingered. Mr Ellison should silence such sniping for good. But Mr Ellison still has plenty of hurdles to clear. Oracle says that it expects the Justice Department's antitrust division soon to rule on the bid. Mr Ellison's declared goal is to secure Oracle's position in a consolidating industry. After years of rapid growth, the software business is maturing around a handful of big firms, such as IBM and Microsoft, says Mr Ellison. To compete, Oracle has to double or even triple in size "fairly rapidly" by buying smaller and weaker rivals. If Oracle cannot buy PeopleSoft, "we'll start buying other people," he adds. A second reason for wanting PeopleSoft is weakness in Oracle's own core business. Mr Ellison made his fortune (which Forbes puts at $18 billion) building database software. Although Oracle has controlled this business for years, it now faces tougher competition. Although Oracle's applications business now absorbs half his firm's software-development costs, Mr Ellison's efforts have so far produced mixed results. The customers and, most importantly, software-maintenance contracts that come with PeopleSoft's applications business (together with that of JD Edwards, a mid-market specialist which PeopleSoft bought last year) should help to salvage Oracle's costly applications investment.